Business Identification Number Licensing Service (A Policy Implementation Study Based on Regent Regulation No. 19 of 2022 Concerning the Delegation of the Regent’s Authority in the Field of Licensing Services to the Investment and One-Stop Integrated Serv - Bambang Suryanto; I Made Weni; Praptining Sukowati (Institute of Educational, Research, and Community Service)
Implementation of policies based on Regent Regulation No. 19 of 2022 concerning the delegation of authority of the Regent in the Field of Licensing Services to the Investment and One-Stop Integrated Services Office of Malang Regency, In general, public services in Malang Regency cannot be separated from geographical conditions, area, population and supporting infrastructure for providing services to the community. The quality and quantity of human resources of service providers, information and knowledge of the community about services and Regional Government regulations regarding public services are also very important to study because they will have an impact on the community. This study aims to describe and analyze the Implementation of the Business Identification Number (NIB) licensing service policy at the Malang Regency Investment and One-Stop Integrated Service Office. This study uses a qualitative descriptive research type with data collection techniques through interviews, documentation, and observation. The results of this study indicate that Malang Regency DPMPTSP has adequate facilities and infrastructure: a large parking lot, an air-conditioned waiting room, chairs available for people to wait, equipped with computers and free wifi, there are clear SOPs and workflows applied by officers, service officers are very responsive to the public, people who take care of NIB get good, friendly, and clear services. The quality of human resources owned is in accordance with the competency needs, but there is still a lack of limited quantity in the Front Office section, the communication flow between leaders and staff is good and helps each other. If the service quality indicators including tangibility, reliability, responsiveness, empathy, and service assurance have been implemented by consensus and supported by a good network, good quality human resources, good coordination flow and high policy consistency, then the service quality will be more effective.